Dinoflagellate Cysts and Acritarchs from the Upper Vardekløft Formation (Jurassic) of Jameson Land, East Greenland. - Sarjeant, William (Meddelelser om Grønland, 1972)
Two assemblages of dinoflagellate cysts and acritarchs are described, from horizons in the Upper Vardekløft Formation of central Jameson Land. 44 species of dinoflagellate cysts are discussed: seven of those (Gonyaulacysta whatleyi, Pareodinia groenlandica, P. apotomocerastes, Meiourogonyaulax callomonii, M. strongylos, ? M. cantrellii and Chytroeisphaeridia dictydia) are described for the first time. In addition, one new variety (Pareodinia ceratophora var. scopaeus) is distinguished and two new combinations (?Acanthaulax spinosissima and Tenua rarispinosa) are proposed. Five species of acritarchs are also mentioned. The assemblages indicate a Bathonian date for the lower horizon (greater precision being scarcely possible in terms of present knowledge of dinoflagellate ranges) and a Middle Callovian (Jason to Athleta) date for the upper horizon. In a supplement, Dr. M. D. Murn presents a brief study of the spores and pollen grains in the two horizons of the Upper Vardekl0ft Formation. She shows them to consist dominantly of long-ranging forms, not capable of providing close stratigraphic dates. 15 species are recognised.